P-160 YI Evaluation of the Serum Levels of the Incretins (GLP-1 and GIP) and DPP-IV in Crohn's Disease. (March 2016) - Magro, Daniela; Calixto, Antonio; Vasques, Ana Carolina; Martinez, Carlos Augusto; Rossi, Debora Helena; Geloneze, Bruno; Pareja, José; Coy, Claudio
Abstract : Background: Gastric-inhibitory polypeptide (GIP), also known as the glucose-dependent insulinotropic peptide, is secreted by the K cells located in the duodenum and proximal jejunum. Glucagon-like-peptide 1 (GLP-1) is secreted by the L cells in the distal part of the small intestine and the colon, as a result of nutrient ingestion, primarily fat and carbohydrates. Both are metabolized by the DPP-IV enzyme (DPP-IV) but their effects in Crohn's disease (CD) are still unknown.[ZERO WIDTH SPACE] Goal: To evaluate the serum levels of the incretins in patients with CD and to correlate these levels with the disease's activity. Methods: Carriers of CD and controls were submitted to serum levels of GIP, GLP-1 and DPP-IV, before and after standard test meal (−15, 0, 15, 30, 45, 60, 90, 120, 150 e 180 minutes) and area under the curve analysis. Dosages of C reactive-protein (CRP) and TNF-alfa were also performed. Patients were classified according to the disease's activity by the CDAI, considering clinical activity for scores higher than 150. Results: The control group (CG) consisted of 7 healthy individuals and 20 carriers of DC were included, 10 in activity (group 1) and 10 in clinical remission (group 2). Group 1 presented higher scores of PCR ( P < 0.001), TNF-alfa ( P < 0.05) in relation to group 2 and CG. The serum levels of GIP are significantly higher in carriers of CD, when compared to the control group, before and after the standard test meal ( P < 0.025). The levels of GLP-1 were higher in group 2, in comparison to group 1 e GC (12.33; 5.61; 4.68, P < 0.025) and the serum levels of DPP-IV found in groups G1, G2 and GC were 2.03; 0.93; 0.87 respectively, however significant between group 2 and GC ( P < 0.024). Conclusions: The intestine's inflammatory process did not interfere in the secretion of GIP, but associated itself to the lowest levels of GLP-1 possibly because of the activity of DPP-IV. FAPESP process 2014/06164-8